Investigating the service provision challenges by healthcare providers in selected comprehensive health centers - Sabaghpoor, Foruzandeh (J Educ Health Promot, 2019)
INTRODUCTION: The healthcare program has opponents and supporters with its multiple policies and also its difficult implementation, which requires that its barriers and problems be addressed comprehensively and extensively. This study was conducted aimed to determine the service provision challenges by healthcare providers, from their point of view, in selected comprehensive health centers of Isfahan. MATERIALS AND METHODS: The present study is a descriptive-analytic one. One-hundred and ninety-seven healthcare providers were selected by census sampling method from the population of female healthcare providers in Isfahan comprehensive health centers in 2017. The data collection tool was a researcher-made questionnaire in the field of individual–professional, managerial–organizational, and executive challenges. Data analysis was done by repeated measures ANOVA and post hoc test. RESULTS: The findings indicated that there was a significant difference between the mean score of individual–professional, managerial–organizational, and executive challenges (P < 0.001) from the point of view of healthcare providers. According to least significant difference post hoc test, the mean score of individual challenges was significantly lower than that of managerial and executive challenges (P < 0.001). However, there was no significant difference between the mean score of managerial–organizational and executive challenges (P = 0.46). CONCLUSION: Based on the results, healthcare providers have put forward several challenges during the implementation of the healthcare program. Meanwhile, executive and managerial challenges have been considered more than individual challenges. Considering that this could lead to improper service provision to the clients, the role of policymakers in this program to remove obstacles and to provide satisfaction to healthcare providers is emphasized.